Tidepool characteristics of nudibranch habitat in Southern California - Richelle L Tanner (PANGAEA, 2025)
Nudibranchs, sea slugs belonging to the Mollusca phylum, reside in rocky intertidal ecosystems worldwide. These intertidal ecosystems are facing significant impacts of climate change, including, in the Eastern Pacific Ocean, an increase in the frequency and severity of El Niño Southern Oscillation (ENSO) weather events. While most organisms are negatively affected by the warm waters that accompany ENSOs, nudibranchs have documented population booms. They are also highly tolerant of thermal extremes, positioning them as important indicators of tidepool health. To address biotic and abiotic conditions that impact nudibranch presence, we investigated ecological factors that affect the microhabitat selection of nudibranchs in tidepools across Southern California in June 2022-January 2023 (ranging across 35.2589°N, 120.8975°W to 32.7269°N, 117.2562°W). We evaluated the environmental and habitat characteristics of 28 tidepools from each of ten field sites each during summer and winter. We also collected species richness data. Tidepool depth and bottom substrate were significantly correlated with nudibranch presence but not temperature. Nudibranchs were more likely to occur in tidepools without, rather than with, sea anemones. Here, we present the first documentation of multivariate abiotic and biotic interactions that influence nudibranch presence.